Enhancing security in generic e-Commerce systems - Mak, Foo Keong. (2010)
e-Commerce has seen a huge growth in revenue for the past decade and with the increasing advancement of today’s technology, e-Commerce system has been prone to a lot of attacks from all over the world. One of the most common security features found in today e-Commerce application is the Secure Socket Layer (SSL) connection and even with SSL alone, it may not be sufficient to withstand hackers’ attacks. It may cause great losses to the store owner if their online store is broken into. This jeopardizes the client’s privacy and caused them to lose confidence to shop online.